Note and Comments: On Putty-Clay: A Comment - Britto, R. (Review of Economic Studies, 1969)
Journal Article Note and Comments: On Putty-Clay: A Comment Get access R. Britto R. Britto University of California, Los Angeles Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 3, July 1969, Pages 395–398, https://doi.org/10.2307/2296435 Published: 01 July 1969 Article history Received: 15 October 1968 Received: 15 January 1969 Published: 01 July 1969